Design and development of magnetic flux leakage capsule - Mastura Norddin (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This final year project focuses on designing a magnetic flux leakage (MFL) capsule with dual diameter. Innovation of this product is for small diameter of pipeline by using wheel system. This In-line inspection tool (ILI) is used for identify the leakage and damage that occurs inside the pipeline. Dual diameter wheeled system is rarely design on small diameter capsule because of the limited space on the capsule. Besides, the different diameter of pipeline will cause user to use two different capsule for small size of diameter.